A CLINICAL STUDY TO EVALUATE THE EFFICACY OF SAINDHAVADI TAILA MATRA VASTI IN THE MANAGEMENT OF AMAVATA W.S.R. RHEUMATOID ARTHRITIS - Negi, Archana; Pandey, Punita; Singh, Bhupinder (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of the study is to find the efficacy of Saindhavadi Taila Matra Vasti in the management of Amavata (rheumatoid arthritis [RA]). Methods: For the present clinical study 15 patients of Amavata (RA) were registered from the Outpatient Department, PG Department of Kayachikitsa, Rishikul Campus, Haridwar. Saindhavadi Taila Matra Vasti was given 60 ml once daily for 8 days, followed by an interval of 7 days. Again Vasti was given once daily for 8 days followed by gap of 7 days. Same cycle was repeated next month. Assessment of the patients was done on the basis of subjective, objective, and functional parameters at the interval of 15 days. Results: Statistically significant result was found in subjective parameters such as pain intensity, Sandhishotha, Gaurav, Apaka (p<0.01 in each), Jwara, Aruchi, and Utsahahani (p<0.05 in each). Statistically non-significant result was found in all the functional parameters (p>0.05), that is, in grip strength, foot pressure, and goniometry. In biochemical parameters, statistically significant result was found in erythrocyte sedimentation rate only (p<0.05). Although non-significant result was found in other biochemical parameters such as hemoglobin, RA factor, and C-reactive protein (CRP) concentration, the mean scores of RA factor and CRP were reduced from 48.7 IU/ml and 10.4 mg/L before treatment to 25.8 IU/ml, 8.2 mg/L after treatment, respectively. Conclusion: In the clinical study, patients got symptomatic relief in many of the complaints but no significant result was found in functional parameters and most of the biochemical parameters. Thus, it can be concluded that Saindhavadi Taila Matra Vasti alone is effective in mild-to-moderate cases of Amavata (RA) and in severe cases it can be used along with oral Ayurvedic formulations for better results.